PELATIHAN BERJALAN DI ATAS BALOK LURUS SEJAUH 8 METER 5 REPETISI 4 SET LEBIH BAIK DARIPADA 4 REPETISI 5 SET TERHADAP KESEIMBANGAN TUBUH MAHASISWA FAKULTAS PENDIDIKAN OLAHRAGA DAN KESEHATAN IKIP PGRI BALI - I G P Ngurah Adi Santika; I P G. Adiatmika; Susy Purnawati (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2015)
The Body Balance of students of the Faculty of Sport Education and Health PGRI Bali tend to decrease. This is supported by preliminary data from the body balance, that the students are in the norm level of balance. The purpose of this study was to determine the effect of walking training on a straight beam 8 m x 10 cm x 30 cm 4 sets of 5 reps increasing student body balance Faculty of Sport Education and Healt Students IKIP PGRI Bali and to investigate the training walk on a straight beam 8 m x 10 cm x 30 cm 4 sets of 5 reps improve body balance is bigger than 4 repetitions 5 sets of students of Faculty of Sport Educatoin and Healt Student IKIP PGRI Bali. This study used a pretest-posttest randomized control group design. A total of 22 students aged 18-23 years were selected as members of the sample were divided into 2 groups. Group I was given a training walk on a straight beam as far as 8 feet 5 repetitions 4 sets and a Group II are trained to walk on a straight block as far as 8 feets 4 repetitions 5 sets. Training was given 4 times a week for 6 weeks. Balancing is measured before and after training use stork balance test. T-test Paired is used to determine the balance mean difference in the balance of each group before and after treatment with a significance level of 0,05, t-independent test to determine the increasing of the body balance. The results showed an increase in of body balance of the group I and group II. The results of test paired in group I the first data is 20,02±2,52 seconds increased 40,10±3,80 seconds in group II the first data is 21,47±5,08 seconds increased 34,59±5,47 seconds by significance level of 0,05 is significantly different. Test Paired results indicate a difference of the intreasing of balance of the group I and group II. Independent test results in group I was 20,08 seconds 50,07% and in group II was 13,12 seconds 37,93%. Based on these results we can conclude that training walk on a straight block as far as 8 meters 5 repetitions 4 sets is more increase balancing walking on the straight block as far as 8 meters 4 repetitions 5 sets.